2019
DOI: 10.3390/jcm8101544
|View full text |Cite
|
Sign up to set email alerts
|

Rotator Cuff Tenocytes Differentiate into Hypertrophic Chondrocyte-Like Cells to Produce Calcium Deposits in an Alkaline Phosphatase-Dependent Manner

Abstract: Calcific tendonitis is a frequent cause of chronic shoulder pain. Its cause is currently poorly known. The objectives of this study were to better characterize the cells and mechanisms involved in depositing apatite crystals in human tendons. Histologic sections of cadaveric calcified tendons were analyzed, and human calcific deposits from patients undergoing lavage of their calcification were obtained to perform infrared spectroscopy and mass spectrometry-based proteomic characterizations. In vitro, the miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…We first observed that synthetic apatite crystals used as control contained larger elements than patients' calcifications. After grinding, we obtained particles with size (1-100 µm length) and morphology (round shape) close to the human calcifications (Figure 1A) [3]. Therefore, we used the grinded synthetic crystals for the following experiments.…”
Section: Pro-inflammatory Effects Of Human Calcifications On Human Monocytes Macrophages and Tenocytesmentioning
confidence: 98%
See 4 more Smart Citations
“…We first observed that synthetic apatite crystals used as control contained larger elements than patients' calcifications. After grinding, we obtained particles with size (1-100 µm length) and morphology (round shape) close to the human calcifications (Figure 1A) [3]. Therefore, we used the grinded synthetic crystals for the following experiments.…”
Section: Pro-inflammatory Effects Of Human Calcifications On Human Monocytes Macrophages and Tenocytesmentioning
confidence: 98%
“…Human crystals from calcific tendonitis were collected from symptomatic patients by ultrasound-guided needle lavage and stored in PBS (phosphate buffered saline) at -80°C as previously described [3]. All patients enrolled gave their formal consent.…”
Section: Crystal Preparationmentioning
confidence: 99%
See 3 more Smart Citations